The Influence of Training, Work Experience, and Work Motivation on Employee Performance at Radio Republik Indonesia Palembang - Zahra Salsabila Nur Atyas; Azwardi; Afriyadi Cahyadi; Zunaidah (PT. INOVASI TEKNOLOGI KOMPUTER, 2026)
This research was conducted to examine the influence of training, work experience, and work motivation on employee performance at Radio Republik Indonesia Palembang. This research used quantitative data analysis to measure whether there was a correlation between the variables. The data collection included primary and secondary data, with questionnaire being the primary data as a tool to record the respondents’ view on the variables. The research population included all 86 employees of Radio Republik Indonesia Palembang, using a saturated sampling technique. The data was analyzed using multiple linear regression analysis. The results show that training was significantly affecting employee performance. This finding implies that training can have an impact on employee performance if there is participation, repetition, relevance, transference, and feedback. On the contrary, work experience has an insignificant effect on employee performance, indicating that long periods of employment do not determine an employee's work experience. Lastly, work motivation has a significant effect on employee performance. This finding suggests that employees that have motivation in the form of need for achievement, need for power, and need for affiliate as their driving force could maintain the intensity, direction, and persistency in achieving the designated performance. The company needs to review employees with long periods of service to determine whether the length of time they have spent in their jobs is in line with the skills and competencies they should have gained from their work experience.